Risiko Kejadian Kanker Serviks Pada Wanita Berdasarkan Faktor Keturunan Di RSUD Gambiran Kota Kediri - Anindita Hasniati Rahmah; Eko Winarti; Trisniwati Trisniwati (VISIKES: Jurnal Kesehatan Masyarakat, 2017)
Cervical cancer is one of the important health problem for women around the world. According to WHO cervical cancer is the most common cancer types. In 2009 the number of cervical cancer cases in East Java reached 1.879 cases consisting of 1.185 people hospitalized and 694 persons outpatient. This was inferential research with case control design, use secondary data from Gambiran Hospital Kediri, 2014. Samples of this study were fifty cervical cancer patients as case group and fifty non cervical cancer patients as control group, selected by simple random sampling method. The result showed that woman with cervical cancer hereditary factorshad risk for having cervical 6,83 time higher than those who had no heredity factor of cervical cancer. (OR: 6,83 (CI 2,73-17,09)Keywords: heredity factors, cervical cancer